The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Structural Health Monitoring 2019 2019
DOI: 10.12783/shm2019/32195
|View full text |Cite
|
Sign up to set email alerts
|

Defect Sizing Using Convolution Neural Network Applied to Guided Wave Imaging

Abstract: The lightweight aluminum alloys are extensively used in the aerospace industry. These materials are used for constructing complex structures such as aircraft fuselage due to their excellent strength-to-weight ratio, stiffness, and corrosion resistance. However, defects such as corrosion or fractures can appear because of thermo-mechanical aging in a hostile working environment or impact forces due to the improper use of these structures. In light of this, Guided Waves (GWs)-based Structural Health Monitoring (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Since the seminal 2012 paper on image classification [50], deep convolutional neural networks (CNN) have shown that they are well adapted to all sorts of image-related tasks. Building upon the previous work [51], we propose to use a CNN network architecture specifically tailored on the scattering matrix data targeting inversion (regression) tasks. In the following, we refer to this architecture as "SMInvNet".…”
Section: ) Convolutional Neural Network For Regressionmentioning
confidence: 99%
“…Since the seminal 2012 paper on image classification [50], deep convolutional neural networks (CNN) have shown that they are well adapted to all sorts of image-related tasks. Building upon the previous work [51], we propose to use a CNN network architecture specifically tailored on the scattering matrix data targeting inversion (regression) tasks. In the following, we refer to this architecture as "SMInvNet".…”
Section: ) Convolutional Neural Network For Regressionmentioning
confidence: 99%